Dermatoethics Contemporary Ethics and Professionalism in Dermatology - Bercovitch, Lionel; Perlis, Clifford; SpringerLink (Online service) (London : Springer London, 2012)
There has been a sea-change in dermatology in the last three decades. Electronic communication, social networking, healthcare reform, the changing reimbursement scene, consumerism and the business of medicine, cosmetic dermatology and medical spas, and advances in genetic technology, all give rise to new ethical concerns. These developments combined with the frailties of human nature, to which physicians are not exempt, underscore the need for ongoing teaching and dialogue on contemporary issues in dermatologic ethics and professionalism. The public, accrediting organizations, and physicians themselves recognize the need for training resources in dermatology ethics and professionalism. Dermatoethics; Contemporary Ethics and Professionalism in Dermatology represents an analysis of real-life case scenarios that is both practical and scholarly. Each chapter deals with a specific topic by presenting one or more case vignettes pertinent to that topic. These topics are relevant for those teaching in ethics, dermatology trainees and practicing dermatologists in academia. The vignettes are followed by a detailed analysis by the chapter author identifying relevant contemporary trends as well as pertinent ethical principles. This book is readable, contemporary, and thought-provoking, yet scholarly and authoritative.
INTRODUCTORY CHAPTER -- Basics of bioethics and ethical analysis -- Codes of professional ethics -- CLINICAL ETHICS -- Medical errors -- Refusal of treatment -- Care of minors -- Privacy and confidentiality -- Electronic communications and teledermatology-ethics in cyberdermatology -- Unsolicited diagnosis -- Fictional illness and psychodermatology -- RESEARCH AND PUBLICATION ETHICS -- Human subjects research and IRBs in dermatology -- Ethical issues in dermatologic genetics-genetic testing, gene patents -- Publication ethics- Ethical issues for writers, editors, and reviewers -- SUBSPECIALTY ETHICAL ISSUES -- Ethical issues in surgical dermatology -- Ethical issues in cosmetic dermatology, including office dispensing, advertising and promotion, ethics of medispas, the dermatologist as entrepreneur -- Ethical issues in dermatopathology -- Ethical issues in industrial dermatology and contact dermatitis -- PROFESSIONAL ETHICS -- Ethical Issues in Specialty Training including: relationship to faculty and patients, the residency match, trainee-industry relationships -- Lying for patients, "gaming the system" and other challenges to honesty -- Professional boundaries -- The impaired or incompetent dermatologist -- Gifts to physicians -- Conflicts of interest and dual loyalties -- Dermatologist-Industry relationships -- Access to care and manpower issues.
Keywords: Medicine; Dermatology; Practice of medicine; Medical ethics; Medicine & Public Health; Dermatology; Theory of Medicine/Bioethics.; Health Administration